Continuum absorption of millimeter waves in nitrogen. (February 2020) - Serov, E.A.; Balashov, A.A.; Tretyakov, M.Yu.; Odintsova, T.A.; Koshelev, M.A.; Chistikov, D.N.; Finenko, A.A.; Lokshtanov, S.E.; Petrov, S.V.; Vigasin, A.A.
Highlights: Nitrogen continuum spectrum is experimentally and theoretically studied under close to atmospheric conditions. Obtained spectra validate previous experimental data and theoretical models. We demonstrate negligible contribution of N2 -N2 bound dimer to the total absorption. Refined set of empirical parameters is derived for the mm-submm radiation propagation models. Abstract: We report the results of experimental study for the N2 absorption in the millimeter wavelength range at pressure and temperature ranging, respectively, from 750 to 1500 Torr and from 265 to 310 K. The obtained data are shown to be in a good agreement with the previously published experimental results, as well as with the predictions issued from available empirical models of nonresonant absorption and from the simulation of the N2 –N2 rototranslational collision-induced absorption performed recently using the classical trajectories method relying on complete ab initio potential and induced dipole surfaces. Analysis of the first spectral moments leads to a conclusion that the role of true bound (N2 )2 dimer absorption is negligible at least in the range of atmospheric temperatures. New experimental data reported in this paper are supported by our theoretical modelling being however somewhat in excess of the data presented in the HITRAN/CIA database for the same spectral range. We consider our data as an update of the previously available so-called "dry" atmospheric continuum which is conventionally employed nowadays in the mm-waves propagation models.